Are odorant constituents of herbal tea transferred into human milk? - Denzer-Lippmann, Melanie; Kirsch, Frauke; Büttner, Andrea (Journal of Agricultural and Food Chemistry, 2015)
The present study investigates aroma transfer from commercial nursing tea, consumed in the maternal diet, into human milk by correlating sensory assessments with quantitative analytical data. The target terpenes were quantified in milk (expressed before and after tea consumption) and tea samples via gas chromatography-mass spectrometry (GC-MS) using stable isotope dilution assays (volunteer donors n = 5). Sensory analyses were carried out on different milk samples from a single donor, sampled before (blank) and at different times after tea ingestion. Quantitative analysis revealed that no significant odorant transfer into milk was observed after lactating women drank the tea. The comparative sensorial analysis of milk samples expressed before and after tea consumption confirmed that tea ingestion had no significant influence on the odor profile of human milk.
UnivIS-Import:2015-07-08:Pub.2015.nat.dchph.llmch.areodo
Keywords: herbal tea; human milk; odorant transfer; SAFE (solvent-assisted flavor evaporation); sensory

Are odorant constituents of herbal tea transferred into human milk? - Denzer, Melanie; Kirsch, Fabian; Büttner, Andrea (Journal of Agricultural and Food Chemistry, 2015)

Development and validation of a food-associated olfactory test (FAOT) - Denzer-Lippmann, Melanie; Beauchamp, Jonathan; Freiherr, Jessica; Thürauf, Norbert; Kornhuber, Johannes; Büttner, Andrea (Chemical Senses, 2017)
Olfactory tests are an important tool in human nutritional research for studying food preferences, yet comprehensive tests dedicated solely to food odors are currently lacking. Therefore, within this study, an innovative food-associated olfactory test (FAOT) system was developed. The FAOT comprises 16 odorant pens that contain representative food odors relating to different macronutrient classes. The test underwent a sensory validation based on identification rate, intensity, hedonic value, and food association scores. The accuracy of the test was further compared to the accuracy of the established Sniffin’ Sticks identification test. The identification rates and intensities of this new FAOT were found to be comparable to the Sniffin’ Sticks olfactory identification test. The odorant pens were also assessed chemo-analytically and were found to be chemically stable for at least 24 weeks. Overall, this new identification test for use in assessing olfaction in a food-associated context is valid both in terms of its use in sensory perception studies and its chemical stability. The FOAT is particularly suited to examinations of the sense of smell regarding food odor
EVALuna2:33556
Keywords: food odorants; identification test; olfactory test; olfaction; PT-MS; smell

Effect of oral bolus versus sustained release application of nutrient solution on olfaction - Denzer-Lippmann, Melanie; Bachlechner, S.; Wielopolski, Jan; Fischer, M.; Büttner, Andrea; Dörfler, Arnd; Schöfl, Christof; Münch, Gerald; Kornhuber, Johannes; Thürauf, Norbert (2016)
EVALuna2:33155

Effects of different isocaloric oral nutrient solutions on olfactory functioning, hunger and food craving - Thürauf, Norbert; Denzer-Lippmann, Melanie; Bachlechner, Stephan; Wielopolski, Jan; Fischer, Marie; Büttner, Andrea; Dörfler, Arnd; Schöfl, Christof; Münch, Gerald; Kornhuber, Johannes (2017)
EVALuna2:33148

Grehlin concentrations correlate with hunger and craving ratings following oral ingestion of macronutrients - Thürauf, Norbert; Bachlechner, Stephan; Denzer-Lippmann, Melanie; Wielopolski, Jan; Fischer, Marie; Büttner, Andrea; Dörfler, Arnd; Schöfl, Christof; Muench, Gerald; Kornhuber, Johannes (CHEMICAL SENSES, 2019)
CRIS-Team WoS Importer:2019-03-26

Quantitative validation of the n-butanol sniffin’ sticks threshold pens. - Denzer, Melanie; Gailer, Stefan; Kern, David W.; Schumm, L. Philip; Thürauf, Norbert; Kornhuber, Johannes; Büttner, Andrea; Beauchamp, Jonathan (Chemosensory Perception, 2014)
Odorant pens are used by medical practitioners and researchers to assess olfactory dysfunction. Despite their routine use, there are currently no data on the gas-phase odorant concentrations released from the pen tips or whether these concentrations scale linearly with the aqueous-phase concentrations inside the pens. The commercially available Sniffin’ Sticks odor threshold test containing n-butanol was chosen for evaluation. The gas-phase concentration of n-butanol at the tip of each pen was measured directly in a new set of pens via proton-transfer-reaction mass spectrometry (PTR-MS). Measurements were additionally made on the same pens after 6 months and two older pen sets, namely a 3-year-old (used) and 4-year-old (new) set. Furthermore, application-related tests were made to determine the performance of the pens during routine use and under stress. These data demonstrate that the gas-phase n-butanol concentrations of the threshold pens are linear over the entire set, both for brand-new pens and 6 months later; this reflects the expected performance that was previously only assumed. Furthermore, the application–simulation tests demonstrated a good performance of the pens when used according to their intended protocol. Measurements of the older pen sets suggest that storage conditions are more critical than usage for pen stability. The present findings confirm that the n-butanol odorant pens are an appropriate tool for threshold testing, provided they are stored and handled correctly.<br

Quantitative validation of the n-butanol Sniffin' Sticks threshold pens - Denzer, Melanie; Gailer, Stefan; Kern, David W.; Schumm, L. Philip; Thürauf, Norbert; Kornhuber, Johannes; Büttner, Andrea; Beauchamp, Jonathan (Chemosensory Perception, 2014)
Odorant pens are used by medical practitioners and researchers to assess olfactory dysfunction. Despite their routine use, there are currently no data on the gas-phase odorant concentrations released from the pen tips or whether these concentrations scale linearly with the aqueous-phase concentrations inside the pens. The commercially available Sniffin' Sticks odor threshold test containing n-butanol was chosen for evaluation. The gas-phase concentration of n-butanol at the tip of each pen was measured directly in a new set of pens via proton-transfer-reaction mass spectrometry (PTR-MS). Measurements were additionally made on the same pens after 6 months and two older pen sets, namely a 3-year-old (used) and 4-year-old (new) set. Furthermore, application-related tests were made to determine the performance of the pens during routine use and under stress. These data demonstrate that the gas-phase n-butanol concentrations of the threshold pens are linear over the entire set, both for brand-new pens and 6 months later; this reflects the expected performance that was previously only assumed. Furthermore, the application-simulation tests demonstrated a good performance of the pens when used according to their intended protocol. Measurements of the older pen sets suggest that storage conditions are more critical than usage for pen stability. The present findings confirm that the n-butanol odorant pens are an appropriate tool for threshold testing, provided they are stored and handled correctly. © 2014 The Author(s).
UnivIS-Import:2015-04-14:Pub.2014.nat.dchph.llmch.quanti
Keywords: n-Butanol; Odor threshold test; Olfaction; PTR-MS; Sniffin' Sticks

The Effects of a Normal Rate versus a Slow Intervalled Rate of Oral Nutrient Intake and Intravenous Low Rate Macronutrient Application on Psychophysical Function - Two Pilot Studies - Denzer-Lippmann, Melanie; Bachlechner, Stephan; Wielopolski, Jan; Fischer, Marie; Büttner, Andrea; Dörfler, Arnd; Schöfl, Christof; Muench, Gerald; Kornhuber, Johannes; Thürauf, Norbert (Frontiers in Psychology, 2017)
Stomach distension and energy per time are factors influencing satiety. Moreover, different rates of nutrient intake induce different stomach distension. The goal of our studies was to elucidate the influence of different oral rates of nutrient intake (normal rate versus slow intervalled rate; study I) and intravenous low rate macronutrient application (protein, carbohydrate, fat) or placebo (study II) on psychophysical function. The pilot studies investigated the effects of 1) study I: a mixed nutrient solution (1/3 protein, 1/3 fat, 1/3 carbohydrates) 2) study II: intravenous macronutrient infusions (protein, carbohydrate, fat) or placebo on psychophysical function (mood, hunger, food craving, alertness, smell intensity ratings and hedonic ratings) in human subjects. In study I 10 male subjects (age range: 21-30 years) completed the study protocol participating in both test conditions and in study II 20 male subjects (age range: 19-41 years) completed the study protocol participating in all test conditions. Additionally, metabolic function was analyzed and cognitive and olfactory tests were conducted twice starting 100 min before the beginning of the intervention and 240 min after. Psychophysical (mood, hunger, fat-, protein-, carbohydrate-, sweets- and vegetable-craving), alertness and metabolic function tests were performed seven times on each examination day. Greater effects on hunger and food cravings were observed for normal rate of intake compared to slow intervalled rate of intake and intravenous low rate macronutrient application. Our findings potentially confirm that volume of the food ingested and a higher rate of energy per time contribute to satiety during normal rate of food intake, while slow intervalled rate of food intake and intravenous low rate macronutrient application showed no effects on satiation. Our results motivate the view that a certain amount of volume of the food ingested and a certain energy per time ratio are necessary to reduce hunger and food craving.
EVALuna2:33741
Keywords: food ingestion; food intake; rate of food intake; psychophysical function; food craving; parenteral food administration; parenteral food intake